Association of the Hospital Volume of Frail Surgical Patients Cared for with Outcomes after Elective, Major Noncardiac Surgery: A Retrospective Population-based Cohort Study. (April 2017) - McIsaac, Daniel I.; Wijeysundera, Duminda N.; Huang, Allen; Bryson, Gregory L.; van Walraven, Carl
Abstract : Background: Frailty is a risk factor for adverse postoperative outcomes. Hospitals that perform higher volumes of surgery have better outcomes than low-volume providers. We hypothesized that frail patients undergoing elective surgery at hospitals that cared for a higher volume of similarly frail patients would have improved outcomes. Methods: We conducted a retrospective, population-based cohort study using linked administrative data in Ontario, Canada. We identified all adult major, elective noncardiac surgery patients who were frail according to the validated Johns Hopkins Adjusted Clinical Groups (ACG ® ) frailty-defining diagnoses indicator. Hospitals were categorized into frailty volume quintiles based on volumes of frail surgical patients cared for. Multilevel, multivariable modeling measured the association of frailty volume with 30-day survival (primary outcome), complications, failure to rescue (secondary outcomes), and costs (tertiary outcome). Results: Of 63, 381 frail patients, 708 (1.1%) died after surgery. The thirty-day mortality rate in the lowest volume quintile was 1.1% compared to 0.9% in the highest. After adjustment for surgical risk, demographic characteristics, comorbidities, and clustering within hospitals, we found a significant association between frailty volume and improved survival (highest volume vs. lowest volume quintile: hazard ratio 0.51; 95% CI, 0.35 to 0.74; P < 0.0001). Although complication rates did not vary significantly between hospitals, failure-to-rescue rates were inversely related to volume. Conclusions: Frail patients have reduced survival and increased failure to rescue when they undergo operations at hospitals having a lower volume of frail surgical patients. Concentration of perioperative care in centers that frequently treat high-risk frail patients could improve population outcomes. Abstract : In a retrospective analysis of 63, 381 frail patients, the authors evaluated the associations between hospital surgical volume of frail patients and 30-day survival. Adjusted survival was significantly improved in the highest volume quintile compared to the lowest: hazard ratio 0.51 (95% CI, 0.35 to 0.74). Survival among frail patients was best in centers that care for large numbers of frail surgical patients.Supplemental Digital Content is available in the text.